Low thermal emissive surface properties of ZnO/polyimide composites prepared by pulsed laser deposition - Babrekar, Harshada A.; Jejurikar, S. M.; Jog, Jyoti Prakash; Adhi, K. P.; Bhoraskar, S. V. (Applied Surface Science, 2011)
We report the low thermal-emissive surface properties of composites of ZnO-polyimide. The composites were synthesized by depositing ZnO on polyimide surface by pulsed laser deposition technique. ZnO target was ablated at different incident energy densities and the substrate (polyimide) was held at elevated temperature. This facilitated the c-axis oriented growth of ZnO, which was inferred from the X-ray diffraction analysis. The composites consisted of multilayers having different electrical resistivities. The values of which are also estimated from Hagen-Rubens relation. The reduced infrared emissivities of the composite films, as compared to polyimide, were correlated to the increased carrier concentration and reduced surface resistivity estimated from the Hall measurements. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: pulsed laser deposition; Thermal emissivity; Thin films; Zinc oxide